Formation of Nanocomposite Solid Oxide Fuel Cell Cathodes by Preferential Clustering of Cations from a Single Polymeric Precursor - Eksioglu, Aycan; Arslan, Leyla Colakerol; Sezen, Meltem; Ow-Yang, Cleva; Büyükaksoy, Aligül (Amer Chemical Soc, 2019)
Conventional composite cathodes used in solid oxide fuel cells (SOFCs) are fabricated by co-sintering of electrocatalyst and ionic conductor powders at 1100-1250 degrees C. The relatively high-temperature heat treatments required to ensure bonding among the powders and between the powders and electrolyte results in the formation of resistive phases and coarse microstructures corresponding to short triple-phase boundary (TPB) length and, consequently, low oxygen reduction activity. In the present work, to achieve long TPBs and avoid resistive phase formation, we propose to fabricate nanocomposite La0.8Sr0.2MnO3-Ce0.8Sm0.2O2 (LSM-SDC) and La0.8Ca0.2MnO3-Ce0.8Sm0.2O2 (LCM-SDC) thin film cathodes by a low-temperature method, which involves the use of a single polymeric precursor solution containing all the respective cations. Owing to the molecular level mixing and the liquid lack of any powder-based starting material, we envision that preferential clustering of cations forming nanoscale electrocatalyst and ionic conductor particles will take place upon heat treatment at relatively low temperatures of 600-800 degrees C. Here, we report for the first time in the literature, a correlation between the heat-treatment temperature-phase evolution-cluster formation-surface chemistry evolution and electrochemical activity of nanocomposite thin film cathodes fabricated from a single polymeric precursor. Our experiments reveal that highest electrochemical activity is achieved when the electrocatalyst phase is poorly crystallized, complete clustering of cations takes place, and A-site dopant segregation at the surface is minimal.
Keywords: solid oxide fuel cell; nanocomposite electrode; polymeric precursor deposition; thin films; impedance spectroscopy; transmission electron microscopy; X-ray photoelectron spectroscopy